Risk Factors associated with In-Hospital Death in Adult COVID-19 Patients in Karachi, Pakistan: A Retrospective Chart Review - Ahmad, Imran; Rathore, Farooq Azam; Khan, Muhammad Nadir; Nazir, Sheikh Nabi Buksh (Pakistan Armed Forces Medical Journal, 2024)
Objective: To identify the risk factors associated with in-hospital mortality of COVID-19 patients in the largest Navy hospitals in Pakistan. Study Design: Retrospective chart review. Place and Duration of Study: Department of Medicine, Pakistan Navy Station Shifa Hospital, Karachi Pakistan, from Apr to May 2020. Methodology: All patients who died in the Intensive care unit of Pakistan Navy Station Shifa Hospital, Karachi during study period, having polymerase chain reaction positive COVID-19 infection were included. The data recorded included basic demographics (age, gender and length of stay in hospital), documentation of co-morbidities (e.g. diabetes mellitus, ischemic heart disease and other medical and surgical problems), need for mechanical ventilation and most probably cause or contributory factor to the death of the patient. Descriptive statistics were used for calculating mean and frequencies. Chi-square test was used to determine the association between variables of the study, Results: A total of 22 cases were included. There were 21 males. The mean age was 65.7 years. Most 12(56.5%) of the patients were more than 65 years of age. Diabetes Mellitus was the most common risk factor in 15(69%) patients followed by hyperten-sion 13(59%) and ischemic heart disease in 10(45%). The hospital admission ranged from 1 to 19 days with a mean of 7.13 days. Conclusion: We identified length of stay, mechanical ventilation, age >65 years, pneumonia and DIC are the potential risk factors for in-hospital mortality in severely ill COVID-19 patients. This audit can guide the clinicians working in resource constrained areas, ....